EFFECT OF SOWING DATE, IRRIGATION REGIME AND MINERAL FERTILIZER RATE ON GRAIN YIELD OF WINTER WHEAT VARIETIES IN SOIL CONDITIONS OF DESERT REGION (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, in the conditions of the barren soils of the desert region of Kashkadarya region, in 2015-2017, the varieties of winter wheat "Zimnitsa" and "Gozgon" were planted in the periods 01-05.10 and 15-20.10, and in their cultivation 70-75-60 and 75-80-70% compared to LFWC irrigation procedures and NPK of mineral fertilizers 100:75:50; The norms of 180:120:90 and 250:175:125 kg/ha, in the conditions of light sierozem soils of the desert region, in the maintenance of winter wheat varieties "Alekseeich", "Bunyodkor" and "Shams" in 2020-2022 compared to LFWC 70-70-60 and 75-80-70% irrigation procedures and NPK of mineral fertilizers- 120:80:60; The analysis of the scientific data obtained on the effect of winter wheat varieties on grain yield when using the norms of 180:120:90 and 240:160:120 kg/ha is presented.